Blood pressure variability and risk of cardiovascular events and death in patients with hypertension and different baseline risks. (20th January 2018) - Mehlum, Maria H; Liestøl, Knut; Kjeldsen, Sverre E; Julius, Stevo; Hua, Tsushung A; Rothwell, Peter M; Mancia, Giuseppe; Parati, Gianfranco; Weber, Michael A; Berge, Eivind
Abstract: Aims: Blood pressure variability is associated with increased risk of cardiovascular events, particularly in high-risk patients. We assessed if variability was associated with increased risk of cardiovascular events and death in hypertensive patients at different risk levels. Methods and results: The Valsartan Antihypertensive Long-term Use Evaluation trial was a randomized controlled trial of valsartan vs. amlodipine in patients with hypertension and different risks of cardiovascular events, followed for a mean of 4.2 years. We calculated standard deviation (SD) of mean systolic blood pressure from visits from 6 months onward in patients with ≥3 visits and no events during the first 6 months. We compared the risk of cardiovascular events in the highest and lowest quintile of visit-to-visit blood pressure variability, using Cox regression. For analysis of death, variability was analysed as a continuous variable. Of 13 803 patients included, 1557 (11.3%) had a cardiovascular event and 1089 (7.9%) died. Patients in the highest quintile of SD had an increased risk of cardiovascular events [hazard ratio (HR) 2.1, 95% confidence interval (95% CI) 1.7–2.4; P < 0.0001], and a 5 mmHg increase in SD of systolic blood pressure was associated with a 10% increase in the risk of death (HR 1.10, 95% CI 1.04–1.17; P = 0.002). Associations were stronger among younger patients and patients with lower systolic blood pressure, and similar between patients with different baseline risks, except for higher risk of death among patients with established cardiovascular disease. Conclusion: Higher visit-to-visit systolic blood pressure variability is associated with increased risk of cardiovascular events in patients with hypertension, irrespective of baseline risk of cardiovascular events. Associations were stronger in younger patients and in those with lower mean systolic blood pressure.